Peningkatan Literasi Keamanan Siber Guru dan Siswa melalui Pelatihan Keamanan Informasi Dasar di Belitung - Wahyuni, Eka Indah (Pakis Journal Institute, 2026)
The increasing dependence on digital technology in educational environments is not always accompanied by adequate data security awareness, making teachers and students vulnerable to cyber threats. This community service aims to improve cybersecurity literacy for secondary school teachers and students in Belitung Regency through basic information security training. The method used is Participatory Technology Development (PTD), which includes theoretical socialization, technical account security workshops, and phishing attack simulations. The program's success was measured through quantitative analysis of pre-test and post-test scores as well as observation of technical behavioral changes. The results showed a significant increase in literacy, with the participants' average score increasing from 52.1 to 85.3 (63% effectiveness). In addition, all participants successfully adopted two-factor authentication (2FA) security features on their devices. This program has successfully provided added value to educational institutions in Belitung in forming a cyber-aware culture as a step toward early protection against digital crime.